ГЛОБАЛЛАШУВ ШАРОИТИДА МАФКУРАВИЙ ЭҲТИЁЖНИНГ ОРТИШИ (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
the fact that fierce battles in the information fields of the 21st century are becoming a tradition, one of the harsh realities of the new century, that a group of evil-intentioned forces that have chosen the path of international terrorism around the world are trying to mislead people in order to achieve their malicious intentions, first of all, simple, educated and life experience It is justified that they try to confuse the minds and thinking of low people with various fabrications.